Cogan-Reese syndrome with Iris cyst: A novel presentation. Issue 4 (August 2019) - Selvan, Harathy; Brar, Anand S.; Angmo, Dewang
Highlights: Iridocorneal endothelial syndrome is a spectrum of disease characterized by unilateral progressive anterior segment changes due to 'epitheloid-like' endothelial cells. The common features of Cogan-Reese syndrome include fine iris nodules, peripheral anterior synechiae, loss of crypts, ectropion uveae and secondary glaucoma. The presentation of Cogan-Reese syndrome with iris cyst in this case is novel, which could be related to the disease pathogenesis, or a rare co-incidental finding. Abstract: Purpose: To report an atypical case of Cogan-Reese syndrome associated with iris cyst in a young adult male. Methods: Slit-lamp biomicroscopic examination, swept-source anterior segment optical coherence tomography (ASOCT) and ultrasound bio-microscopy (UBM) were done to evaluate and characterize the nature of the iris cyst. Gonioscopy, specular microscopy and confocal microscopy were attempted, but unsuccessful due to the large corneal opacity. Results: On slit-lamp biomicroscopy, a large nasal corneal opacity with overlying band-shaped keratopathy was noted, with history suggestive of a trivial non-penetrating trauma and likely healed corneal ulcer. Through the temporal clear cornea, the iris displayed altered pattern with overlying shiny membrane and multiple, small, discrete, hyperpigmented, irregular nodules suggestive of Cogan-Reese syndrome. On the nasal side, an iris cyst with typical 'stuck-on appearance' onto the endothelium was visible. ASOCT and UBM failed to show any evidence of epithelial downgrowth or Descemet membrane disintegrity, ruling out the possibility of a post-traumatic implantation iris cyst. Conclusion: The occurrence of iris cyst in this case of Cogan-Reese syndrome is unique, and could be related to the disease pathogenesis, or a rare co-incidental finding.